Mermas de combustibles líquidos y su relación con el proceso de tributación en estaciones de servicio de Punchana año 2022 - Tafur Tapullima, Junior Albertine (2023)
The present investigation had the objective of determining that the wastes of liquid fuels are related to the process of taxation in the service stations in the district of Punchana year 2022. The research methodology comprised a basic type, correlational and non-experimental design, probabilistic sampling, population of 34 workers among the service stations in the district of Punchana, as well as a sample of 32 actors of such population group. The most important results showed that the liquid fuel losses of Gasoline 90, Diesel B2 and Gasoline 84 are generated during the plant-to-tanker, tank-to-tanker and pump-to-customer supply procedures, while the taxation process of the service stations in the district of Punchana involves duly complying with their tax obligations, making deductions in their income tax according to a series of normative criteria, as well as observing their right to claim, appeal and contentious-administrative action within the framework of the contentious-tax procedure. Finally, the main conclusion was that it has been determined that the wastage of liquid fuels is significantly related to the taxation process in the service stations in the district of Punchana year 2022, being this conclusion conditioned with Spearman's correlation standard 0.910, which was collected for the general working hypothesis.